Response of a Truss SPAR Offshore Platform to Environmental Loads (case study : Kikeh Field at Sabah Waters) - Chyrina binti Mohamed Zamri, Chyrina (Universiti Teknologi Petronas, 2010)
The experimental results on the scale model of the first Malaysian SPAR offshore platform are presented and analysed. The structure, called Kikeh SPAR, has been designed by overseas consultant, constructed locally in Malaysia and installed in Sabah waters in 2006. The study targets to fill a vacuum in the design of such important structures by conducting physical modeling. The properties of the scale model are known from several tests. Varying the conditions of wave and current, allows the calibration of force in x-direction. Changing the wave height, wave period, and ballast conditions, a series of laboratory tests was achieved at 20m x 10m x 1.2m wave basin of the Coastal Engineering Laboratory, Universiti Teknologi PETRONAS, under regular and random waves while SPAR is moored by 10 mooring lines connected to the basin floor. The dynamic response of the SPAR was monitored by photographic methods and the heave, surge and pitch of the structure were plotted vs. time. The analysis of the maximum responses showed the significance of the wave period and ballast condition. The scale modeling data show a satisfactory similarity with the prototype.